Gangrene after penicillin injection (a case report) - Ozel, A; Yavuz, H; Erkul, I (The Turkish Journal of Pediatrics, 1995)
A patient with right lower limb gangrene that developed after penicillin injection is presented. Accidental intraarterial administration of penicillin may cause gangrene necessitating amputation. To avoid this severe complication, every intramuscular injection should be given with meticulous attention to proper technique, with adequate restraint of the patient, and with full knowledge of local anatomy and potential complications.